High Prevalence of Genital Human Papillomavirus Infection in Patients With Primary Immunodeficiencies - Gernert, Michael; Kiesel, Matthias; Fröhlich, Matthias; Renner, Regina; Strunz, Patrick-Pascal; Portegys, Jan; Tony, Hans-Peter; Schmalzing, Marc; Schwaneck, Eva Christina (Frontiers in Immunology, 2021)
Background Genital human papillomavirus (HPV)-infections are common in the general population and are responsible for relevant numbers of epithelial malignancies. Much data on the HPV-prevalence is available for secondary immunodeficiencies, especially for patients with human immunodeficiency virus (HIV)-infection. Little is known about the genital HPV-prevalence in patients with primary immunodeficiencies (PIDs). Methods We performed a cross-sectional study of patients with PIDs and took genital swabs from male and female patients, which were analyzed with polymerase chain reaction for the presence of HPV-DNA. Clinical and laboratory data was collected to identify risk factors. Results 28 PID patients were included in this study. 10 of 28 (35.7%) had HPV-DNA in their genital swabs. 6 patients had high-risk HPV-types (21.4%). Most patients had asymptomatic HPV-infections, as genital warts were rare (2 of 28 patients) and HPV-associated malignancy was absent. Differences in the HPV-positivity regarding clinical PID-diagnosis, duration of PID, age, sex, immunosuppression, immunoglobulin replacement, or circumcision in males were not present. HPV-positive PID patients had higher numbers of T cells (CD3+), of cytotoxic T cells (CD3+/CD8+), of transitional B cells (CD19+/CD38++/CD10+/IgD+), and of plasmablasts (CD19+/CD38+/CD27++/IgD-) compared to HPV-negative. Conclusion PID patients exhibit a high rate of genital HPV-infections with a high rate of high-risk HPV-types. Regular screening for symptomatic genital HPV-infection and HPV-associated malignancy in PID patients seems recommendable.